Helical folding of poly(naphthalenecarboxamide) in apolar solvent. Issue 3 (27th November 2012) - Mikami, Koichiro; Yokozawa, Tsutomu
<x xml:space="preserve">Abstract</x> Helical folding of poly(naphthalenecarboxamide)s with aliphatic side chains in hydrophobic solvents is investigated. The CD spectra of the polyamide showed a predominant left‐handed helical structure in chloroform, THF, and cyclohexane. Furthermore, the sergeants and soldiers experiment in cyclohexane showed a clear chiral amplification. These results indicate that the helical structure was stabilized by an intramolecualr self‐association based on the solvophobic effect, and that there is cooperativity between the monomer units constituting the helical structure. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>